(3OjhGf eMeO GdcQjejs - (3eMeO Hh jhSa GdcQjej,J (B1068 (3g` s
(3ChdgG (B:s
(3hHYO(B: (3agPG OjhGf eMeO CafOj GdcQjej aef Pdc bhdg QMeg Gddg JYGdi hGbYg MGd, hgj HSe Gddg GdQMef GdQMje CbQC Gddg Yjf Yjfj s
(3BNQgG (B:s
(3ef bUjOI jeOM HgG GdSGOI GdYeGOjI, hegfFkG dg HGdEaJGA CQLh HXgQ GdZjH Whd MjGJce UObG eOMj HGdOYG eNJhe s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfjs
(3GfXQg eY OjhGf SYOGdOjf Hf YQHjs
(3jdj GdOjhGf YOI CTYGQ dTYQGA eNJdajf aj (B15 (3hQbIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B31 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B134 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B287s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B204 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs